The Factors Affecting Continuance Intention of ChatGPT as An AI Chatbot in Indonesia - Mahury, Rivan Andriawan; Neneng Nurlaela Arief (Social Science Studies, 2024)
The transition from Industry 4.0 into Industry 5.0 is happening somehow. That case also appeared in Indonesia. Currently during 2023 there is this Artificial Intelligence Chatbot been developed by OpenAI and released at November, 2022. This AI Chatbot named ChatGPT mainly functioned to allow human for having conversation with Chatbot itself. The problem occurred in Indonesia is that whether personal information of the user given to this Chatbot secured or not and does the user is still willing to continue using this Chatbot after they know the security and risk of cybercrime for their own personal information. This research used Quantitative-method and used an online survey to collect data with the total respondent of 30 respondents that used to get the Preliminary Data Analysis for the Paper. This paper is also using Smart PLS to calculate the data and the purpose of this research is to identify and test whether the factors between variables are having significant relation to the use of ChatGPT App in Indonesia. Result showed that there were no significant relation between each variables towards the Continuance Intention of ChatGPT App in Indonesia.